Diagnosing Adolescence From Curing Adolescents to Caring for Young People - Ellis, Wesley W. (2018)
Scholars have been defining adolescence throughout the history of youth ministry, but the nature and function of the term's application has often remained unexamined. The practice of diagnosis provides the appropriate metaphor for the activity in which practitioners and theologians engage when they apply "adolescence" to the experience of young people. Drawing from the field of disability theology, the author exposes some of the potential dehumanizing pitfalls of a diagnostic approach and seeks to reorient youth ministry toward the Christological praxis of caring for young people as opposed to the diagnostic practice of resolving or "curing" adolescents.
Keywords: Christopraxis; Youth Ministry; Adolescence; Diagnosis; disability theology